A Public Law Perspective on Intellectual Property. (22nd August 2014) - French, Robert
<x xml:space="preserve">Abstract</x> This paper, delivered as the Annual Francis Gurry Lecture at Melbourne University in 2012, considers intellectual property law as a species of public law serving public purposes. The purposes reflecting the interests of creators, owners and users of intellectual property rights are in tension. That tension affects the normative clarity of intellectual property law and its effective enforcement. It may inform the construction of intellectual property statutes and the application of evaluative criteria of validity under those statutes. In Australia, intellectual property statutes are made under constitutional authority with respect to specified categories of intellectual property, the specific content of which may vary with technological change. Official decisions effecting the creation or discontinuance in intellectual property rights are statutory and subject to constitutionally based judicial review in addition to particular appeal rights conferred by statute. At the heart of the public law aspect of intellectual property rights is a tension between their characterisation as proprietary or instrumental.